The effects of egg weight and shape index on hatching characteristics in bronze turkeys - Erisir, Z; Ozbey, O (Indian Veterinary Journal, 2005)
Eggs are the main factor ensuring the continuation of poultry breed. Thus characteristics of the egg are of extreme importance. The internal and external quality of the egg influence. hatchability, chick quality and, the productivity characteristics (Nestor et al., 1972). The size of the egg directly influences the results of hatching. The shape index is reported to have limited effects on hatchability (Christensen and Nestor, 1994; Baspinar et al. 1997), has identified important and negative correlations between the shape index and the weight of the egg. Therefore this study has been made to find out the influence of egg weight and shape index on hatching features in Bronze Turkeys.